(untitled) (Research, Society and Development, 2020)
The Basic Education Development Index (IDEB) represents an educational indicator measured by the National Institute of Educational Studies and Research (INEP) to assess the quality of Brazilian schools. Its composition is analyzed through the school flow and learning performance in Portuguese and Mathematics compiled by the Basic Education Assessment System (SAEB). In this perspective, the present research compared the observed and projected IDEB, of the state schools of Northern Brazil and the State of Amapá between 2007 and 2017 and it was found that the State of Amapá still has a learning performance deficit in relation to the average other states in the North of Brazil. In view of the above, the article suggests that IDEB fulfills its social function described in goal 7 of the National Education Plan (PNE), which treats the indicator as a guideline for public policies to be implemented in school life.